Investigation of Some Factors, Influencing the Level of Performance and Relative Performance of Top Olympic Weightlifters - Szabo, Andras S; Adamfi, Attila (Journal of Sports Research, 2017)
For characterization of the performance level of top weightlifter the world records (achieved till 31.12.2016.) were used. The relative performance was determined as the ratio of the records and own bodyweight (category weight). It is demonstrated that both in case of male and female lifters the performance and the relative performance depend on the body-mass, however the tendency is opposite. Theoretically the performance is the function of body-mass on the 2/3 power, so it increases with the body-mass, but the relative performance decreases as a function of body-mass on the minus 1/3 power. Evaluating the results in the clean and jerk (C&J) we have to take into account the own bodyweight of the lifters, as well, because the lifters lift during the execution of the C&J attempt the barbell + the own body, standing up from squatting position. So the weigfhtlifter lifts not only the barbell, but also his/her own bodyweight! The results with this correction show rather good agreement with the theoretically determined performance ratios for the different (8+7) weight categories.